(untitled) (Journal of Fiber Bioengineering and Informatics, 2023)
At present, the intelligent design of clothing patterns still needs to rely on the experience of the pattern maker, and it cannot liberate the pattern maker from the complicated design work. The efficiency and flexibility of the design of clothing patterns are not high. In order to realize the intelligent pattern design of design knowledge automation, a directed graph method is proposed to construct a clothing pattern design model, and the model is used to analyze the clothing pattern. In view of the characteristics of clothing pattern design, the directed graph method is used to record the pattern design process, and the model of clothing pattern design is constructed. The model is accurately analyzed by decomposing the original model of clothing pattern design into sub-models of each structural line. Application examples verify the feasibility of constructing a pattern design model and application by the directed graph method. The research results show that the pattern design model can clearly express the pattern design process and the valuable experience involved, and can accurately and quickly analyze the pattern. This research can provide a way to extract, collect, process, share and reuse pattern design knowledge for intelligent clothing design, and improve the efficiency of clothing pattern design.